Safe and efficient management systems for plantation pests and diseases - Tuck Ho Cheng (Planter, 1998)
Safe amd efficient management systems for plantation pests and diseases should ideally have no deleterious side effects and be self-sustaining. Three such systems are described, i.e. the use of beneficial plants for natural suppression of bagworms in oil palms, prolonging productivity of Ganoderma infected oil palms by soil mounding and treatment with vesicular-arbuscular mycorrhizal (VAM) fungi, and the use of raised nurseries and organic soil amendments to manage nematode infection of guava. For the first, natural suppression of Metisa plana infestation of oil palm by planting of nectariferous Euphorbia heterophylla and Antigonon leptopus was successfully demonstrated. For the second, soil mounding alone was seen to be the most cost effective method of prolonging productivity of prime-aged oil palm, with 58 per cent more yield being realised within 36 months. Use of VAM fungal treatment brought about 42 to 68 per cent increase in yield. There is great potential in combining the two treatments for greater effectiveness. The use of nurseries with guava planting materials being raised above ground level was seen to be able to significantly reduce consequential infection of such material by the root knot nematode Meloidogyne incognita. This has decreased subsequent field mortality of such planting material by 24 per cent. Organic soil amendments, particularly the use of oil palm empty fruit bunches, was demonstrated to provide superior control of nematode damage to field planted guava than conventional nematicide application.